The Effect of Independence, Transparency, and Audit Experience on Audit Quality with Auditor Competency as a Moderation Variable (Study on Public Companies in Indonesia for the 2021-2023 Period) - Sitohang, Kezia; Prietycillia, Joyce (CV. Civiliza Publishing, 2025)
This study aims to analyze the influence of auditor independence, audit transparency, audit experience, and auditor competence on audit quality. The background of this research is based on the importance of the role of auditors in providing confidence in the fairness of financial statements presented by business entities. The higher the quality of the audit carried out, the greater the level of trust of stakeholders in the company's financial information. This study uses a quantitative approach with causal design, as well as multiple linear regression analysis techniques to test the relationships between variables. The data was collected through the distribution of questionnaires to auditors working at Public Accounting Firms (KAP) in Indonesia. The results showed that partially or simultaneously, the four independent variables had a significant effect on audit quality. These findings confirm that increased auditor independence, transparency, experience, and competence are crucial factors in creating reliable and high-quality audits. The implications of this study are expected to be an input for regulators, companies, and auditors in improving audit quality through improving individual and institutional aspects of auditors.